2016
DOI: 10.1007/s00267-016-0796-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Spatial Distribution of Metal(Oid)s in Soils Around an Abandoned Pb-Smelter Plant

Abstract: Todos os Santos (All Saints) Bay area, NE-Brazil, is known for one of the most important cases of urban lead (Pb) contamination in the world. The main objective of this work was to assess and interpret the spatial distribution of As, Cd, Hg, Pb, and Zn in "background" soils of this environmentally impacted bay area, using a combination of geostatistical and multivariate analytical methods to distinguish between natural and anthropogenic sources of those metal(oid)s in soils. We collected 114 topsoil samples (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition to the distance from the pollutant source and the presence of afforestation, physicochemical characteristics are also important to evaluate the interaction capacity between soils and metals, as they influence soil adsorption capacity (Denaix et al, 2001;Kabata-Pendias and Pendias, 2001). Dos Santos et al (2017) observed that clay soils showed higher Pb and Zn concentrations than sandy soils when exposed to identical anthropogenic sources. Tume et al (2018b), in turn, found a positive correlation between Pb concentrations and organic matter content.…”
Section: Quantitative Analysis and Contamination Levelmentioning
confidence: 99%
“…In addition to the distance from the pollutant source and the presence of afforestation, physicochemical characteristics are also important to evaluate the interaction capacity between soils and metals, as they influence soil adsorption capacity (Denaix et al, 2001;Kabata-Pendias and Pendias, 2001). Dos Santos et al (2017) observed that clay soils showed higher Pb and Zn concentrations than sandy soils when exposed to identical anthropogenic sources. Tume et al (2018b), in turn, found a positive correlation between Pb concentrations and organic matter content.…”
Section: Quantitative Analysis and Contamination Levelmentioning
confidence: 99%
“…Environmental contamination by lead (Pb) could originate from anthropogenic sources such as sewage sludge, mining, metallurgy, or waste and pollutant emissions from various industrial activities. Once Pb enters the soil system, it can be transferred to various trophic levels, compromising environmental quality (Ren, Wang, & Zhang, 2006;Gamiño-Gutiérrez, González-Pérez, Gonsebatt, & Monroy-Fernández, 2013;Li, Lin, Cheng, Duan, & Lei, 2015;Santos, Nascimento, Matschullat, & Olinda, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, quanto maior a quantidade de argila, maior a CTC do solo(Adriano, 2001). DosSantos et al (2017) verificaram que solos argilosos apresentaram concentrações superiores de Pb e Zn em relação a solos arenosos expostos as mesmas fontes antrópicas. JáTume et al, (2018a), verificaram uma correlação positiva entre Pb e conteúdo de matéria orgânica.…”
unclassified